An Updated Evaluation of the Dichotomous Link Between Creativity and Mental Health - Zhao, Rongjun; Tang, Zhiwen; Lu, Fang; Xing, Qiang; Shen, Wangbing (Frontiers in Psychiatry, 2022)
The theory of the mad genius, a popular cultural fixture for centuries, has received widespread attention in the behavioral sciences. Focusing on a longstanding debate over whether creativity and mental health are positively or negatively correlated, this study first summarized recent relevant studies and meta-analyses and then provided an updated evaluation of this correlation by describing a new and useful perspective for considering the relationship between creativity and mental health. Here, a modified version of the dual-pathway model of creativity was developed to explain the seemingly paradoxical relationship between creativity and mental health. This model can greatly enrich the scientific understanding of the so-called mad genius controversy and further promote the scientific exploration of the link between creativity and mental health or psychopathology.